Penentuan Format Penulisan Laporan Ilmiah yang Ergonomis pada Media Kertas untuk Mengefisienkan Penggunaan Kertas. (Studi Kasus pada Mahasiswa Universitas Ma Chung Malang) - Novenda Kartika Putrianto (Jurnal Rekayasa Sistem Industri, 2022)
Paper usage in Universities leads to a large amount of paper waste. An adjustment of writing format without overriding ergonomic aspects is a legitimate way of using paper more efficiently. Three factors affect reading comprehension i.e line length, spacing, and font size. The experimental design 2 × 3 × 2 complete randomized design (CRD) had been proposed and twelve combinations of treatments in the form of writing format had been tried out to respondents. Each treatment was repeated three times and each respondent only got one treatment. The best writing format is line length 10.2 cm, spacing 2, and font size 12 point. Paper savings that can be done using the suggested format compared to the currently used writing format in University is 40% and 25%, while the efficiency is 46.95% and 21.02%.